Photonic crystals and photocatalysis : Study of titania inverse opals - Lebrun, Delphine Misao (Uppsala universitet, Fasta tillståndets fysik, 2016)
Due to an increase of human activity, an increase health risk has emerged from the presence of pollutants in the environment. In the transition to renewable and sustainable life style, treatment of pollutants could support the shifting societies. A motivation behind material research for environmental applications is to maximize the efficiency of the materials to alleviate environmental pollution. In the case of titania, an increase of ultra-violet light absorption is needed to overcome its bandgap to produce reactive radicals, which is the basis for photocatalysis. It has been hypothesized that photonic crystal can enhance titania photocatalysis. They are structures made of at least two dielectrics with a high refractive index contrast, ordered in a periodic fashion. For a strong contrast, photonic band gaps emerge. The effect of the photonic band gap is to force complete reflection of the incoming light within its range and multiple internal reflections at its edges. By combining photonic and electronic band gap positions, it is possible to increase the absorption at the photonic band gap edges. In this thesis, fabrication method and structural analysis of titania and alumina/titania photonic structures were presented. A thorough optical analysis was performed at all steps of fabrication – beyond what previously has been reported. The photocatalytic activity was measured with two setups. Fourier Transform Infrared spectroscopy combined with arc lamps and bandpass filters was used to monitor the degradation of stearic acid in ambient air. A home-built setup was used to degrade methylene blue in solution with ultra-violet illumination. The results in this thesis show in general no correlation of the photocatalytic activity to the photonic band gap position, even though absorbance data displayed an increase absorption in this energy range. A more controlled environment might show the effect of the structure, as seen in some of the experiments.